Bortezomib Treatment to Potentiate the Anti-tumor Immunity of Ex-vivo Expanded Adoptively Infused Autologous Natural Killer Cells - Lundqvist, Andreas (Ivyspring International Publisher, 2011)
Our results show that using an EBV-LCL feeder cell line, large numbers of pure populations of highly activated NK cells can be expanded ex vivo under GMP conditions. With the exception of thyroiditis and constitutional symptoms related to IL-2 therapy, infusions of up to 1 x 10(8) cells/kg of ex vivo expanded NK have been well tolerated and have provided preliminary clinical evidence for mediating anti-tumor immunity in patients with advanced cancer.